Current Concepts in Hip Preservation Surgery: Part II—Rehabilitation. (January 2016) - Adler, Kelly L.; Cook, P. Christopher; Geisler, Paul R.; Yen, Yi-Meng; Giordano, Brian D.
Context: Successful treatment of nonarthritic hip pain in young athletic individuals remains a challenge. A growing fund of clinical knowledge has paralleled technical innovations that have enabled hip preservation surgeons to address a multitude of structural variations of the proximal femur and acetabulum and concomitant intra-articular joint pathology. Often, a combination of open and arthroscopic techniques are necessary to treat more complex pathomorphologies. Peri- and postoperative recovery after such procedures can pose a substantial challenge to the patient, and a dedicated, thoughtful approach may reduce setbacks, limit morbidity, and help optimize functional outcomes. Evidence Acquisition: PubMed and CINAHL databases were searched to identify relevant scientific and review articles through December 2014 using the search terms hip preservation, labrum, surgical dislocation, femoroacetabular impingement, postoperative rehabilitation, peri-acetabular osteotomy, and rotational osteotomy . Reference lists of included articles were reviewed to locate additional references of interest. Study Design: Clinical review. Level of Evidence: Level 4. Results: Hip preservation procedures and appropriate rehabilitation have allowed individuals to return to a physically active lifestyle. Conclusion: Effective postoperative rehabilitation must consider modifications and precautions specific to the particular surgical techniques used. Proper postoperative rehabilitation after hip preservation surgery may help optimize functional recovery and maximize clinical success and patient satisfaction.